Polyaniline-intercalated manganese dioxide nanolayers as a high-performance cathode material for an aqueous zinc-ion battery - Huang, Jianhang; Wang, Zhuo; Hou, Mengyan; Dong, Xiaoli; Liu, Yao; Wang, Yonggang; Xia, Yongyao (Nature communications, 2018)
Rechargeable zinc–manganese dioxide batteries that use mild aqueous electrolytes are attracting extensive attention due to high energy density and environmental friendliness. Unfortunately, manganese dioxide suffers from substantial phase changes (e.g., from initial α-, β-, or γ-phase to a layered structure and subsequent structural collapse) during cycling, leading to very poor stability at high charge/discharge depth. Herein, cyclability is improved by the design of a polyaniline-intercalated layered manganese dioxide, in which the polymer-strengthened layered structure and nanoscale size of manganese dioxide serves to eliminate phase changes and facilitate charge storage. Accordingly, an unprecedented stability of 200 cycles with at a high capacity of 280 mA h g −1 (i.e., 90% utilization of the theoretical capacity of manganese dioxide) is achieved, as well as a long-term stability of 5000 cycles at a  utilization of 40%. The encouraging performance sheds light on the design of advanced cathodes for aqueous zinc-ion batteries. Zn-MnO 2 batteries offer high energy density, but phase changes that lead to poor cathode stability hinder development of rechargeable versions. Here the authors report structurally reinforced polyaniline-intercalated MnO 2 nanolayers that boost performance by eliminating phase transformation.